2008
DOI: 10.1086/588842
|View full text |Cite
|
Sign up to set email alerts
|

Varicella‐Zoster Virus and Cerebral Aneurysm: Case Report and Review of the Literature

Abstract: We report a case of varicella-zoster vasculopathy that occurred in a 42-year-old renal transplant recipient with concurrent vertebral artery aneurysm and dissection. The patient was successfully treated with embolization and acyclovir therapy. Here, we review the English literature regarding the association of varicella-zoster virus infection with cerebral aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…3,4 When presence of VZV was investigated it mainly involved measuring active viral replication via CSF PCR, which, as discussed below, may not always be relevant. Nevertheless, there are several cases where VZV antigen was not histologically detected and where HIV was identified in the vessel wall by immune-histochemistry (anti-gp41) or PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 When presence of VZV was investigated it mainly involved measuring active viral replication via CSF PCR, which, as discussed below, may not always be relevant. Nevertheless, there are several cases where VZV antigen was not histologically detected and where HIV was identified in the vessel wall by immune-histochemistry (anti-gp41) or PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Fusiform aneurysmal dilatation is less common. 3 Recently Nagel et al 6 described 3 histologically confirmed cases of stroke due to varicella vasculopathy. These were both early (4 weeks after VZV infection) and late VZV (48 weeks after infection) vascular presentations and showed surprisingly widespread involvement of cerebral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and occlusions of the extra-cranial vessels like common carotid arteries, central retinal artery occlusion, internal carotid artery occlusion, thrombosis, and vasospasm [17,18].…”
Section: Herpes Zoster Opthalmicus With Hemiplegia Due To Vasculopathymentioning
confidence: 99%
“…Three further cases of aneurysm caused by VZV infection in patients with AIDS were recently reported [24]. In another case of VZV vasculopathy, a 42-year-old renal transplant recipient with concurrent vertebral-artery aneurysm and dissection was successfully treated with embolisation and acyclovir therapy [25]. Most remarkable is the recent report of a patient with zoster in multiple dermatomes, severe headache and normal MRA and 4-vessel digital subtraction angiogram who developed 9 anterior circulation aneurysms 2 months later; antiviral treatment resulted in clinical improvement, size reduction of most aneurysms and complete resolution of the two largest aneurysms [26].…”
Section: Aneurysm/hemorrhagementioning
confidence: 99%